PENERAPAN MODEL PEMBELAJARAN INQUIRY BASED LEARNING (IBL) UNTUK MENINGKATKAN HASIL BELAJAR - Teddy Zulvoya; Nofri Yuhelman; Jumriana Rahayu Ningsih (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
This class action research is motivated by the low learning outcomes of chemistry especially thecolloidal system material. This study aims to improve student learning outcomes through InquiryBased Learning. This type of research is Classroom Action Research (CAR). The research instrumentsused were observation sheets, and tests. Subjects in the study were students of class XIMIA SMAN 2, TelukKuantan, with a total of 21 students. The results showed that the averagecompleteness of individuals in the first cycle was 77.61, with the percentage of classical completenessstudent learning outcomes was 61.90%, in the second cycle the average individual completenesswas 87.14 with the percentage of classical completeness student learning outcomes that is90.47% From these results it can be concluded that the Inquiry Based Learning (IBL) learningmodel on the colloidal system material can improve student learning outcomes in class XI MIASMA N 2 TelukKuantan.